Simulation of activated sludge treatment using ASIM 1 version 3.0 with extant kinetic biodegradation parameters - Torres, Wilma S. (2001)
These parameter estimates were used along with process information to generate simulations into the ASIM ver. 3.0 software. Actual influent COD values from facility records were also inputted. Chi-square (X²) tests were run at a confidence level of α =0.05. The simulation runs were successful in predicting effluent COD values if influent conditions were within 75% of the typical influent COD. However, simulations generated using influent COD values more than 75% of typical influent COD were observed to have significant discrepancies between the predicted and actual COD values. Further studies are recommended on how ASIM can model the impact of shock load variations on enffluent COD. The assumption of Monod kinetics may need to be re-evaluated for high COD concentrations, which inhibit biodegradation. Finally, sampling techniques may need to be redefined to provide a better basis for simulation comparisons.